Morphological Test of Areca Nut Fiber Ceramic Membrane Using Scanning Electron Microscopy Energy Dispersive X-ray Mapping Spectroscopy - Marzain, Amelia; Kalsum, Siti Umi; Marhadi, Marhadi; Shahab, Ahmad Nabil (Journal of Materials Exploration and Findings, 2025)
This study investigates the potential of ceramic membranes derived from areca nut fiber as a cost-effective and environmentally sustainable material for the removal of iron (Fe) and manganese (Mn) from groundwater. Two types of membranes were fabricated: one without activation and one chemically activated using 10% sodium hydroxide (NaOH). The morphological and elemental characteristics of both membranes were analyzed using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX) mapping. The concentrations of Fe and Mn before and after treatment were measured using Atomic Absorption Spectroscopy (AAS). The NaOH-activated membrane exhibited a more porous surface structure and higher oxygen content, which enhanced its adsorption capability. This membrane achieved removal efficiencies of 55.94% for Fe and 67.72% for Mn- substantially higher than the non-activated variant. The results confirm the effectiveness of NaOH activation in enhancing membrane performance and demonstrate the potential of areca nut fiber as a valuable agricultural waste material for low-cost water purification in rural areas.